A summary of the first 100 neurointerventional procedures performed with the Rist radial access device in a Finnish neurovascular center - Rautio Riitta; Alpay Kemal; Rahi Melissa; Sinisalo Matias (ELSEVIER IRELAND LTD, 2025)
Background and purpose: Transradial access (TRA) has increased popularity among neurointerventionalists during a short time period but until recently there have been no devices designed especially for radial use.
Materials and methods: Consecutive neurointerventional procedures with an intention to perform TRA with the Rist radial access guide catheter between April 2021 and May 2022 were retrospectively reviewed. Possible access site complications, other procedure-related complications and information on successful catherization of the target vessel as well as whether the procedure had been successful were collected.
Results: Information from 100 patients was included in the study. The most general procedure was flow diversion (29%) followed by WEB embolization (20 %). Four patients (4%) needed conversion to femoral access. The triaxial system was used in 76% of the procedures. Four patients (4%) experienced access site or device related complications, none of those were serious. Six patients had clinically relevant procedure related complications.
Conclusions: It is concluded that the Rist device can be used safely for a large variety of neurointerventions with a short learning curve.